Physical activity during adolescence and the development of cam morphology: a cross-sectional cohort study of 210 individuals. Issue 9 (10th August 2017) - Palmer, Antony; Fernquest, Scott; Gimpel, Mo; Birchall, Richard; Judge, Andrew; Broomfield, John; Newton, Julia; Wotherspoon, Mark; Carr, Andrew; Glyn-Jones, Sion
Abstract : Introduction: Cam morphology is a strong risk factor for the development of hip pain and osteoarthritis. It is increasingly thought to develop in association with intense physical activity during youth; however, the aetiology remains uncertain. The study aim was to characterise the effect of physical activity on morphological hip development during adolescence. Methods: Cross-sectional study of individuals aged 9–18 years recruited from Southampton Football Club Academy (103 male) with an age-matched control population (52 males and 55 females). Assessments included questionnaires and 3 Tesla MRI of both hips. Alpha angle, epiphyseal extension and epiphyseal tilt were measured on radial images. Results: Alpha angle and epiphyseal extension increased most rapidly between ages 12 and 14 years. Soft-tissue hypertrophy at the femoral head-neck junction preceded osseous cam morphology and was first evident at age 10 years. The greatest increase and highest absolute values of alpha angle and epiphyseal extension were colocalised at 1 o'clock. Maximum alpha angles were 6.7 degrees greater in males than females (p=0.005). Compared with individuals who play no regular sport, alpha angles were 4.0 degrees higher in individuals who play sport for a school or club (p=0.041) and 7.7 degrees higher in individuals competing at a national or international level (p=0.035). There was no association with leg dominance . Conclusions: Sporting activity during adolescence is strongly associated with the development of cam morphology secondary to epiphyseal hypertrophy and extension with a dose-response relationship. Males participating in competitive sport are at particularly elevated risk of developing cam morphology and secondary hip pathology.